A General Model of Author "Style" with Application to the UK House of Commons, 1935–2018. (24th July 2020) - Huang, Leslie; Perry, Patrick O.; Spirling, Arthur
Abstract : We consider evidence for the assertion that backbench members of parliament (MPs) in the UK have become less distinctive from one another in terms of their speech. Noting that this claim has considerable normative and substantive implications, we review theory and findings in the area, which are ultimately ambiguous on this question. We then provide a new statistical model of distinctiveness that extends traditional efforts to statistically characterize the "style" of authors and apply it to a corpus of Hansard speeches from 1935 to 2018. In the aggregate, we find no evidence for the claim of more homogeneity. But this hides intriguing covariate effects: at the MP-level, panel regression results demonstrate that on average, more senior backbenchers tend to be less "different" in speech terms. We also show, however, that this pattern is changing: in recent times, it is more experienced MPs who speak most distinctively.